Dispelling Myths Surrounding AAC Use for Children: Recommendations for Professionals. Issue 1 (February 2023) - Jensen, Emily; Douglas, Sarah N.; Gerde, Hope K.
Augmentative and alternative communication (AAC) includes methods and technologies to support communication and aid individuals with limited speech. There are many widespread misconceptions about AAC use, however, that can negatively impact how children with disabilities are taught in classrooms. In this article, we describe the main types of AAC systems and how they are used to promote child success. Then, we identify and dispel common myths about AAC use and provide evidence-based recommendations for practitioners to support children who use AAC in the classroom.